2015
DOI: 10.1039/c5ra03363b
|View full text |Cite
|
Sign up to set email alerts
|

Design of a graphene oxide-SnO2 nanocomposite with superior catalytic efficiency for the synthesis of β-enaminones and β-enaminoesters

Abstract: A graphene oxide (GO)-SnO 2 -based nanocomposite was synthesized by decorating the graphene oxide surface with SnO 2 nanoparticles via a solvothermal process. The nanocomposite was characterized using Fourier transform infrared spectra (FTIR), FT-Raman spectroscopy, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Field-emission Scanning electron microscopy (FE-SEM), Energy dispersive X-ray spectroscopy (EDS), Transmission electron microscopy (TEM) and N 2 adsorption/ desorption study. The FE-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 88 publications
2
26
0
Order By: Relevance
“…Figure c and 4d represent the FTIR spectrum of the remaining two samples IrO 2 @MTO‐S and Pt@MTO‐S, where the characteristic broad peak ranging from 3400–3450 cm −1 was appeared (Figures a and 4b). Furthermore, in all the samples Sn−O−Sn symmetric stretching at 668 cm −1 and Sn−O asymmetric stretching at 539 cm −1 have been observed . The signal appears at 1633 cm −1 could be attributed to the stretching vibration of the surface adsorbed water molecule for each sample.…”
Section: Resultsmentioning
confidence: 72%
“…Figure c and 4d represent the FTIR spectrum of the remaining two samples IrO 2 @MTO‐S and Pt@MTO‐S, where the characteristic broad peak ranging from 3400–3450 cm −1 was appeared (Figures a and 4b). Furthermore, in all the samples Sn−O−Sn symmetric stretching at 668 cm −1 and Sn−O asymmetric stretching at 539 cm −1 have been observed . The signal appears at 1633 cm −1 could be attributed to the stretching vibration of the surface adsorbed water molecule for each sample.…”
Section: Resultsmentioning
confidence: 72%
“…Various metal oxides nanoparticles such as Fe 3 O 4 34 , CoFe 2 O 4 35 , ZnFe 2 O 4 36 , TiO 2 37 , SnO 2 38 and ZnO 39 were loaded on graphene oxide (GO) sheets, generating highly active and selective catalysts. Recently, our group designed graphene oxide–SnO 2 nanocomposite (GO–SnO 2 ) and used it as an efficient catalyst for the β-enaminones synthesis 40 . Considering the benefits associated with both CuFe 2 O 4 nanoparticles and GO, the combination of GO with CuFe 2 O 4 would form a potential catalytic material and more recently, few studies have corroborated this fact 27 41 .…”
mentioning
confidence: 99%
“…The band at * 616 cm -1 can be assigned to the anti-symmetric O-Sn-O stretching mode of SnO 2 , and band at * 520 cm -1 is due to terminal oxygen vibration in SnO 2 nanostructures. Seema et al [25], Kumar et al [26], Tan et al [27] and Kumar et al [28] also demonstrated similar stretching vibrations in SnO 2 nanostructures. Therefore, the presence of characteristics bands of CdO and SnO 2 in CdO-SnO 2 nanocomposites clearly indicates the incorporation of SnO 2 nanostructures in the CdO nanostructures.…”
Section: Ftir Analysismentioning
confidence: 79%